BNIP‐2 binds phosphatidylserine, localizes to vesicles, and is transported by kinesin‐1. (3rd December 2014) - Akamatsu, Rie; Ishida‐Kitagawa, Norihiro; Aoyama, Takane; Oka, Chio; Kawaichi, Masashi
<x xml:space="preserve">Abstract</x> BNIP‐2 shows high homology with the Cayman ataxia protein, caytaxin, which functions as a kinesin‐1 adapter bridging cargos and kinesin light chains (KLCs). BNIP‐2 is known to induce cell shape changes when over‐expressed in culture cells, but its physiological functions are mostly unknown. BNIP‐2 interacts with KLC through the conserved WED motif in the N‐terminal region of BNIP‐2. Interaction with KLC and transportation by kinesin‐1 are essential for over‐expressed BNIP‐2 to elongate cells and induce cellular processes. Endogenous BNIP‐2 localizes to the Golgi apparatus, early and recycling endosomes and mitochondria, aligned with microtubules, and moves at a speed compatible with kinesin‐1 transportation. The CRAL–TRIO domain of BNIP‐2 specifically interacts with phosphatidylserine, and the vesicular localization of BNIP‐2 requires interaction with this phospholipid. BNIP‐2 mutants which do not bind phosphatidylserine do not induce morphological changes in cells. These data show that similar to caytaxin, BNIP‐2 is a kinesin‐1 adapter involved in vesicular transportation in the cytoplasm and that association with cargos depends on interaction of the CRAL–TRIO domain with membrane phosphatidylserine.